2013
DOI: 10.1186/1471-2164-14-175
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the biology of swine respiratory tract mycoplasmas from a comparative genome analysis

Abstract: BackgroundMycoplasma hyopneumoniae, Mycoplasma flocculare and Mycoplasma hyorhinis live in swine respiratory tracts. M. flocculare, a commensal bacterium, is genetically closely related to M. hyopneumoniae, the causative agent of enzootic porcine pneumonia. M. hyorhinis is also pathogenic, causing polyserositis and arthritis. In this work, we present the genome sequences of M. flocculare and M. hyopneumoniae strain 7422, and we compare these genomes with the genomes of other M. hyoponeumoniae strain and to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 105 publications
3
73
1
1
Order By: Relevance
“…However, other authors have demonstrated, using complete genome analysis, a possible role for sexual reproduction in the evolution of M. agalactiae (33). Moreover, recent studies have shown how recombination is directly involved in the evolution of members of the Mycoplasma mycoides cluster (34), as well as the porcine mycoplasmas M. hyopneumoniae and Mycoplasma flocculare (35). Given the extreme relatedness to M. agalactiae and the evidence of the effects of recombination in the evolution of other mycoplasmas, it is possible that M. bovis has followed a similar evolutionary pathway and therefore the lack of recombination observed after LIAN analysis can be explained by the choice of the housekeeping genes analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have demonstrated, using complete genome analysis, a possible role for sexual reproduction in the evolution of M. agalactiae (33). Moreover, recent studies have shown how recombination is directly involved in the evolution of members of the Mycoplasma mycoides cluster (34), as well as the porcine mycoplasmas M. hyopneumoniae and Mycoplasma flocculare (35). Given the extreme relatedness to M. agalactiae and the evidence of the effects of recombination in the evolution of other mycoplasmas, it is possible that M. bovis has followed a similar evolutionary pathway and therefore the lack of recombination observed after LIAN analysis can be explained by the choice of the housekeeping genes analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic comparative analyzes demonstrated that the sets of adhesin-encoding genes from M. hyopneumoniae 7448 and J, and M. flocculare are quite similar, containing few qualitative differences between the adhesin repertoires of M. hyopneumoniae and M. flocculare [9]. The only differences are the absence of M. flocculare orthologs for one P97 paralog (P97 copy-1, MHP7448_0198), and one P102 paralog (P102 copy-1, MHP7448_0199), and some rearrangements in M. hyopneumoniae genomic regions containing adhesin genes in comparison to M. flocculare .…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between the genomes of M. hyopneumoniae pathogenic and non-pathogenic strains (7448 and J, respectively) revealed no extensive genomic differences [7]. Moreover, previous comparative phylogenetic and phylogenomic studies provided evidences of the close relationship of M. hyopneumoniae and M. flocculare [79], which share most of the known virulence-related genes [10]. The differences between M. hyopneumoniae and M. flocculare include the absence, in M. flocculare , of the glpO gene, related to M. hyopneumoniae hydrogen peroxide generation and cytotoxicity [11,12], and differential domains between orthologs from the P97 family of adhesins and from other surface proteins [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, M. hyorhinis growth is faster than M. hyopneumoniae. Siqueira et al (2013) showed the presence of metabolic genes in the M. hyorhinis genome that are absent in M. hyopneumoniae, suggesting a possible factor associated with the in vitro growth of this species.…”
Section: Discussionmentioning
confidence: 99%